Correlation of the Emergency Medicine Resident In-service Examination with the American Osteopathic Board of Emergency Medicine Part I - David Levy; Ronald Dvorkin; Adam Schwartz; Steven Zimmerman; Feiming Li (Western Journal of Emergency Medicine, 2014)
Introduction: Eligible residents during their fourth postgraduate year (PGY-4) of emergency medicine (EM) residency training who seek specialty board certification in emergency medicine may take the American Osteopathic Board of Emergency Medicine (AOBEM) Part 1 Board Certifying Examination (AOBEM Part 1). All residents enrolled in an osteopathic EM residency training program are required to take the EM Resident In-service Examination (RISE) annually. Our aim was to correlate resident performance on the RISE with performance on the AOBEM Part 1. The study group consisted of osteopathic EM residents in their PGY-4 year of training who took both examinations during that same year.